(untitled) (Islamic Sciences Journal, 2023)
The purposes of the Sharia are the goals and the wisdoms, which the legislator set at each of its rulings, or most of them, in order to achieve them for the benefit of the people. The Messenger of how to pledge allegiance to the people of concealment and chastity, and to avoid the people of deviation and misguidance. Whoever wants to obey the command of his Lord, follow his Prophet, may Allah bless him and grant him peace, and follow the path of his family and companions, may Allah be pleased with them; Let him nourish his heart and mind with the Noble Qur’an, but that is by looking into the purposes of the Shari’a, to the extent of preserving the consideration of the Noble Qur’an, and researching its rulings and meanings.